Disparities in female urologic case distribution with new subspecialty certification and surgeon gender. Issue 2 (17th December 2015) - Liu, Joceline S.; Dickmeyer, Laura Jo; Nettey, Oluwarotimi; Hofer, Matthias D.; Flury, Sarah C.; Kielb, Stephanie J.
Abstract : Aims: To examine surgical case volume characteristics in certifying urologists associated with common female urologic procedures to evaluate the practice patterns, given the recent establishment of subspecialty certification in Female Pelvic Medicine and Reconstructive Surgery (FPMRS) and changes in urologist gender composition. Methods: Six‐month case log data of certifying urologists (2003–2013) was obtained from the American Board of Urology (ABU). We examined case logs for 26 CPT codes for common female urologic procedures focused on four procedure groups: incontinence, prolapse, vesicovaginal fistula (VVF), and revision/removal of vaginal mesh/graft. Results: Among 4802 urologists logging at least one female urology case, 43, 949 (55.6% of all cases) incontinence, 30, 983 (39.2%) prolapse, 451 (0.6%) VVF, and 3643 (4.6%) revision of mesh/graft surgeries were identified. While 90.8% logging at least one female CPT code were men, women surgeons (9.2%) accounted for a disproportionate volume (22.6%) of cases. With initiation of the FPMRS subspecialty certification in 2011, 225 FPMRS candidates (out of 1716 certifying urologists) were identified, compared to 367 (out of 3828 certifying urologists) female subspecialists prior to 2011. FPMRS accounted for 56.7% of prolapse, 62.9% VVF, 59.0% mesh/graft revisions, and 41.9% of incontinence surgeries, compared to female specialists before 2011 (39.1%, 42.4%, 41.5%, and 21.6% respectively (all P  < 0.001)). Conclusions: A growing proportion of female urologic cases are performed by female subspecialists, with a significant increase since initiation of FPMRS subspecialty certification. Women surgeons account for a disproportionate volume of these cases despite remaining a minority of certifying urologists and female subspecialists. Neurourol. Urodynam. 36:399–403, 2017 . © 2015 Wiley Periodicals, Inc.